Immunogenicity of a killed bivalent whole cell oral cholera vaccine in forcibly displaced Myanmar nationals in Cox's Bazar, Bangladesh. - Fahima Chowdhury; Taufiqur Rahman Bhuiyan; Afroza Akter; Md Saruar Bhuiyan; Ashraful Islam Khan; Motaher Hossain; Imam Tauheed; Tasnuva Ahmed; Shaumik Islam; Tanzeem Ahmed Rafique; Shah Alam Siddique; Nabila Binta Harun; et al. (Public Library of Science (PLoS), 2020)
After the large influx of Rohingya nationals (termed Forcibly Displaced Myanmar National; FDMN) from Rakhine State of Myanmar to Cox's Bazar in Bangladesh, it was apparent that outbreaks of cholera was very likely in this setting where people were living under adverse water and sanitation conditions. Large campaigns of oral cholera vaccine (OCV) were carried out as a preemptive measure to control cholera epidemics. The aim of the study was to evaluate the immune responses of healthy adults and children after administration of two doses of OCV at 14 days interval in FDMN population and compare with the response observed in Bangladeshi's vaccinated earlier. A cross-sectional immunogenicity study was conducted among FDMNs of three age cohort; in adults (18+years; n = 83), in older children (6-17 years; n = 63) and in younger children (1-5 years; n = 80). Capillary blood was collected at three time points to measure vibriocidal antibodies using either plasma or dried blood spot (DBS) specimens. There was a significant increase of responder frequency of vibriocidal antibody titer at day 14 in all groups for Vibrio cholerae O1 (Ogawa/Inaba: adults-64%/64%, older children-70%/89% and younger children-51%/75%). There was no overall difference of vibriocidal antibody titer between FDMN and Bangladeshi population at baseline (p = 0.07-0.08) and at day 14, day 28 in all age groups for both serotypes. The seroconversion rate and geometric mean titer (GMT) of either serotype were comparable using both plasma and DBS specimens. These results showed that OCV is capable of inducing robust immune responses in adults and children among the FDMN population which is comparable to that seen in Bangladeshi participants in different age groups or that reported from other cholera endemic countries. Our results also suggest that the displaced population were exposed to V. cholerae prior to seeking shelter in Bangladesh.